2015
DOI: 10.3390/ma8074273
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Surface Photocatalytic Activity with NiO/TiO2 Nanocomposite Structure

Abstract: This study achieved a nanocomposite structure of nickel oxide (NiO)/titanium dioxide (TiO2) heterojunction on a TiO2 film surface. The photocatalytic activity of this structure evaluated by decomposing methylene blue (MB) solution was strongly correlated to the conductive behavior of the NiO film. A p-type NiO film of high concentration in contact with the native n-type TiO2 film, which resulted in a strong inner electrical field to effectively separate the photogenerated electron-hole pairs, exhibited a much … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 39 publications
2
12
0
Order By: Relevance
“…Sim et al reported 86% of the degradation efficiency using plasma enhanced chemical vapor deposition (PECVD) with hydro-oxygenated amorphous titanium dioxide obtained from titanium tetra-isopropoxide [Ti(OC3H7)4, TTIP] liquid as a precursor [ 41 ]. Finally, Chen et al reported 86% catalytic degradation of MB using a method that involves incipient wet impregnation of the nickel oxide (NiO) nanoparticles over previously prepared TiO 2 nanotubes [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sim et al reported 86% of the degradation efficiency using plasma enhanced chemical vapor deposition (PECVD) with hydro-oxygenated amorphous titanium dioxide obtained from titanium tetra-isopropoxide [Ti(OC3H7)4, TTIP] liquid as a precursor [ 41 ]. Finally, Chen et al reported 86% catalytic degradation of MB using a method that involves incipient wet impregnation of the nickel oxide (NiO) nanoparticles over previously prepared TiO 2 nanotubes [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…This method can be also used to prepare NiO//M x O y composites using SiO 2 , TiO 2 , Al 2 O 3 , or Na 4.2 Ca 2.8 (Si 6 O 18 ) matrices. Although a few methods were proposed to prepare NiO/SiO 2 [ 4 , 21 , 22 ], NiO/TiO 2 [ 6 , 23 , 24 , 25 ], NiO/Al 2 O 3 [ 26 , 27 , 28 , 29 ] composites, none of them is as general and simple as the one described here. As for the Na 4.2 Ca 2.8 (Si 6 O 18 ) case, although this particular composition has not been reported, similar nickel oxide doped with silica matrices have been successfully synthesized via a sol–gel process [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…32 It has previously been demonstrated in literature that the addition of NiO to TiO 2 and the subsequent formation of a p-n junction prolongs photogenerated hole-electron lifetimes and increases PEC performance. 11,[33][34][35] As noted earlier, many factors such as film thickness, crystallinity, phase matching at grain boundaries, will all have a profound effect on the photocatalytic performance. However, the most significant factor by far is the p-type conductivity of the NiO.…”
Section: Resultsmentioning
confidence: 95%
“…In turn, TiO 2 is a well-known and widely used photocatalysis for water purification and splitting [33][34][35]. Its photocatalytic activity can be further enhanced by creating various types of composite materials with metals [12,34], sulfides [36][37][38][39], oxides and clays [40][41][42], or by varying the shape of TiO 2 nanoparticles [43][44][45]. In our present study, we used molecular layer deposition technique [46,47] with subsequent hydrolysis to obtain TiO 2 phase on Mg 3 Si 2 O 5 (OH) 4 nanotubes.…”
Section: Introductionmentioning
confidence: 99%